PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW SMP NEGERI 1 GIDO TAHUN PELAJARAN 2014/2015 - Harefa, Amin Otoni (J-PiMat : Jurnal Pendidikan Matematika, 2020)
Abstract. This reseach is aimed to: (1) Describe quality of learning mathematics by using Cooperative Learning model, especially Jigsaw Type. (2) Describe the result of learning mathematics by using Cooperative Learning model, especially Jigsaw Type.The findings of this reseach were: (1) The averrage of result of questionnaire of learning quality by using Cooperative Learning model, especially Jigsaw Type. In the first cycle was 92,28%, the second cycle was 8825%,and the third cycle was 90,21%. So, the averrage was 90,25% (Excellent Predicate), (2) The averrage of the students’ learning outcomes by using Cooperative Learning model, especially Jigsaw Type in the first cycle was 30,23 (Poor), the second cycle was 43,28 (Poor), and the third cycle was 52,43 (Fair).Keyword: Cooperative Learning Model by using Jigsaw Type   Abstrak. Tujuan Penelitian: 1. Mendeskripsikan Kualitas Pembelajaran Matematika dengan menggunakan model pembelajaran Kooperatif Tipe Jigsau, 2. Mendeskripsikan Hasil Belajar Matematika dengan menggunakan model pembelajaran Kooperatif Tipe Jigsau. Hasil Penelitian: 1. Rata-rata Hasil Angket Kualitas Pembelajaran dengan menerapkan Model Pembelajaran Kooperatif Tipe Jigsau pada Siklus I adalah 92,28%, Siklus II adalah 88,25%, dan pada Siklus III adalah 90,21% sehingga rata-rata adalah 90,25%(Amat Baik), 2. Rata-rata Hasil Belajar dengan menerapkan Model Pembelajaran Kooperatif Tipe Jigsau pada Siklus I  adalah 30,23 (Sangat Kurang), pada Siklus II adalah 43,28 (Sangat Kurang), dan pada Siklus III adalah 52,43 (Cukup). Kata Kunci: Model Pembelajaran Kooperatif Tipe Jigsaw